Days of defeat and victory - Gaĭdar, E. T. (Egor Timurovich) (Jackson School publications in international studies., 1999)
"Yegor Gaidar, one of Russia's first post-Soviet prime ministers and principal architect of its historic transformation to a market economy, here presents his account of governing in the tumultuous early 1990s. Though still in his forties, Gaidar has already played a pivotal role in contemporary Russian political history, championing the cause of dramatic economic reform, aggressive privatization of state enterprises, and painful fiscal discipline in the face of widespread popular resistance."--Jacket